Agronomic performance of velvet bean at different spatial arrangement - Silva, Aijânio Gomes de Brito; Guerra, José Guilherme Marinho; Gonçalves Junior, Murilo; Costa, Janaína Ribeiro; Espíndola, José Antonio Azevedo; Araújo, Ednaldo da Silva (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of different plant spatial arrangements on agronomic performance of velvet-bean (Mucuna pruriens var. utilis). The experiment was performed with eight treatments, distributed in a randomized complete block design in a 2x4 factorial arrangement, with four replicates. The treatments were velvet bean sowing at two spacings between furrows (0.5 and 1.0 m) and four plant densities (2, 4, 8 and 16 plants m-1). Determinations were made for the soil covering and biological nitrogen fixation (BNF) rates, and for the dry matter yield and N accumulation in the plant shoots. Total soil cover was accomplished at 50 days after sowing at 16 plants m-1 density and 0.5 m spacing between furrows. The combination of 16 plants m-1 density with the 1.0 m spacing between furrows provided the greatest dry matter yield and accumulated most N in the plant shoots. Irrespective of the plant spatial arrangement, the estimation of BNF in this species shows that about 70% N present in the shoot is derived from the atmosphere.